Fieldworker reflections on using telephone voice calls to conduct fieldwork amidst the Covid-19 pandemic. Issue 4 (2nd October 2021) - Serekoane, Motsaathebe; Marais, Lochner; Pienaar, Michael; Sharp, Carla; Cloete, Jan; Blomerus, Liezel
Abstract : The declaration of Covid-19 as a global pandemic on 11 March, 2020, and the disaster management regulations implemented in reply to it had enormous ramifications on ethnographic fieldwork. This situation presented an opportunity to reconsider the methodology used in a research project on lived experiences of childhood health and well-being in Free State province, South Africa. This study explores the argument that technology can establish a virtual space that fieldworker and research participant can treat as "real." It uses fieldwork diaries and insights to evaluate the benefits and disadvantages of telephonic virtual conversations as a replacement for conventional face-to-face fieldwork to access inaccessible fieldwork sites. It adopts a reflexive qualitative case-study approach to document the experiences of two fieldworkers moving from on-site fieldwork to telephone voice calls to conduct their research. By offering a reflexive account of these technology-mediated fieldwork experiences, this article proposes this methodology as possible alternative to documenting lived experience. Lessons from this experience can contribute to reviewing the traditional practice of ethnographic fieldwork and imagining alternative and complementary methodological possibilities.